A reading of Emily Dickinson - Wilson, Ian (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1970)
From Chapter 1: Even before the publication of The Poems of Emily Dickinson in the variorum edition by Harvard University in 1955, under the editorship of Thomas H. Johnson, there was a steadily growing interest in the work of this poet and in her position both in the sphere of American literature and in the larger field of English poetry. In 1957, The Letters of Emily Dickinson appeared, with Johnson as editor, and Theodora Ward as associate editor. With this publication critical literature received an incentive to increase and extend the exploration already undertaken.
Keywords: Dickinson, Emily, 1830-1886